ChemInform Abstract: Extending the Scope of the Aza‐Fischer Synthesis of 4‐ and 6‐Azaindoles. Issue 45 (14th October 2013) - Thomae, David; Jeanty, Matthieu; Coste, Jerome; Guillaumet, Gerald; Suzenet, Franck
Abstract The cascade reaction of the Fischer synthesis can be efficiently applied to the formation of 4‐ and 6‐azaindoles using microwave irradiation.